Differing dietary patterns according to body composition - Lee, Yea-Chan; Kim, Hyung-Mi; Lee, Hye Sun; Jeon, Soyoung; Kwon, Yu-Jin; Lee, Ji-Won (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to investigate dietary patterns in relation to body composition, categorized into four groups using large-scale nationwide data: neither low muscle mass nor high body fat (N), low muscle mass only (LMo), high body fat only (HFo), and low muscle mass with high body fat (LMHF).MethodsA total of 15,917 participants from the 2008–2011 Korea National Health and Nutrition Examination Survey were analyzed. Propensity score matching (PSM) values, representing the predicted probability of patients having LMo, HFo, or LMHF, were estimated using logistic regression analysis while adjusting for confounders. Analysis of covariance was then used to compare daily macronutrient intake and weekly consumption frequency of food groups among the study groups, adjusting for total calorie intake.ResultsParticipants in the LMHF and HFo groups consumed lower amounts of carbohydrates and higher proportions of proteins and fats compared to the N group. Those in the LMHF and LMo groups had less frequent consumption of rice and vegetables and more frequent intake of ultra-processed foods. Additionally, participants in the LMo and HFo groups consumed beverages more frequently than those in the N group.ConclusionImbalances in body composition, such as LMo, HFo, and LMHF, are associated with less favorable dietary patterns, including higher consumption of ultra-processed foods and beverages, and lower intake of rice and vegetables. Further research is needed to explore targeted nutritional interventions for these groups.